Designing and fabricating a 5G Antenna for wireless mobile applications - Yateem, Jassim (2021)
The mobile and wireless communications industry has evolved steadily over the past decade, from analog 1G to digital systems such as 2G, and then wireless networking at high data rate as 3G. The evolution of communication did not end there, but kept its speed of growth to 3.5 G, then 4G. Today, 5G pilot trials are in progress and the network is planned to be launched in the 2020s. The next generation of wireless mobile communication (5G) is required to fulfil the specifications of a previous form of communication device. With today's growing applications and demands, the lack of spectrum is growing. The use of frequency bands beyond what is used today is therefore expected in the near future. The 5G comes with better efficiency, higher data rate, lower latency and more. The microstrip antenna is one of the most used antennas in 5G communications and plays a critical role in fastest growing wireless communication. We need a conformal, lightweight, cheap and easy-to-produce antenna to create communication between wireless devices on higher frequency bands such as the mm-waveband. Due to their advantages over other antennas, printed antennas are favored. But the gain and bandwidth are lower. These features are significantly enhanced by many methods such as the integration of metamaterials (MTMs) based slot. The metamaterial has unique properties, including negative permittivity and permeability values, negative refractive indices, reverse wave propagation and so on. MTM is commonly used by its many applications to greatly improve the efficiency and characteristics of the microstrip antenna. In this project, a dual band microstrip antennas is designed and implemented for the 5G wireless communications. The duality is influenced by metamaterial technique to generate an additional band. The proposed antenna operates at 28GHz and 34GHz, two of the selected bands allocated to 5G by International Telecommunications Union. The whole design has been simulated utilizing the Microwave Studio CST ver. 18 simulator. The antenna being proposed is highly efficient and suitable for 5G wireless communication.